Rebuilding a realistic corticostriatal “social network” from dissociated cells - Garcia-Munoz, Marianela; Taillefer, Eddy; Pnini, Reuven; Vickers, Catherine; Miller, Jonathan; Arbuthnott, Gordon W. (Frontiers in Systems Neuroscience, 2015)
Many of the methods available for the study of cortical influences on striatal neurons have serious problems. In vivo the connectivity is so sparse that the study of individual cortical inputs to striatum is nearly impossible. Mixed corticostriatal cultures develop many connections from striatal cells to cortical cells, in striking contrast to the fact that only connections from cortical cells to striatal cells are present in vivo. And interneuron populations are over-represented in organotypic cultures. For these reasons, we have developed a method for growing cortical and striatal neurons in separated compartments that allows cortical neurons to innervate striatal cells in culture. The method works equally well for acutely dissociated or cryopreserved neurons and allows a number of manipulations that are not otherwise possible. Either cortical or striatal compartment can be transfected with channel rhodopsins. The activity of both areas can be recorded in multielectrode arrays or individual patch recordings from pairs of cells. Finally, corticostriatal connections can be severed acutely. This procedure enables determination of the importance of corticostriatal interaction in the resting pattern of activity. These cultures also facilitate development of sensitive analytical network methods to track connectivity.